2021
DOI: 10.3390/v13091804
|View full text |Cite
|
Sign up to set email alerts
|

Construction, Identification and Analysis of the Interaction Network of African Swine Fever Virus MGF360-9L with Host Proteins

Abstract: African swine fever virus (ASFV) is prevalent in many countries and is a contagious and lethal virus that infects pigs, posing a threat to the global pig industry and public health. The interaction between the virus and the host is key to unlocking the mystery behind viral pathogenesis. A comprehensive understanding of the viral and host protein interaction may provide clues for developing new antiviral strategies. Here, we show a network of ASFV MGF360-9L protein interactions in porcine kidney (PK-15) cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…The sequences used were as follows: ASFV- P72 -R: 5′-CTGCTCATGGTATCAATCTTATCGA-3′; ASFV- P72 -F: 5′-GATACCACAAGATCAGCCGT-3′; and TaqMan: 5′-CCACGGGAGGAATACCAACCCAGTG-3′. The ASFV genome copy number was calculated using the standard curve [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…The sequences used were as follows: ASFV- P72 -R: 5′-CTGCTCATGGTATCAATCTTATCGA-3′; ASFV- P72 -F: 5′-GATACCACAAGATCAGCCGT-3′; and TaqMan: 5′-CCACGGGAGGAATACCAACCCAGTG-3′. The ASFV genome copy number was calculated using the standard curve [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Then, the protein bands corresponding to the empty vector and MGF110-7L-Flag pulldown lanes that differed in staining intensity were excised from the gel and subsequently subjected to in-gel tryptic digestion to extract peptides for further LC-MS/MS analysis. LC-MS/MS analysis was performed as described previously ( 54 ). After the monoisotopic mass lists for each protonated peptide were obtained, protein identification and quantification were carried out using Mascot 2.3.02 (MatrixScience, London, UK) against the Swiss-Prot Homo sapiens sequence database.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Oh et al (2021) compared MA-104 to the renal-derived swine macrophages; they observed that MA-104 is less able to isolate the field virus, although both wild-type (MW039157) and cell-adapted (MW287337) ASFV genotype II strains grew efficiently in this continuous cell line [ 50 ]. This cell line was also efficiently used to study the interaction network of ASFV with host proteins [ 99 ] and to determine the mechanisms used by ASFV to evade the host innate immune responses [ 100 ].…”
Section: Monkey-derived Continuous Cell Linesmentioning
confidence: 99%